Pseudo-Spectral MPSP-Based Unified Midcourse and Terminal Guidance for Reentry Targets - Sharma, Prayag; Kumar, Prem; Padhi, Radhakant (IEEE transactions on aerospace and electronic systems, 2023)
A unified optimal guidance scheme is presented in this article for both midcourse and terminal phases combined. It minimizes the total deceleration resulting in enhanced range and/or higher impact velocity, while satisfying the terminal constraints on impact angle and miss distance. State-dependent terms are included in the cost function of the recently proposed generalized quasi-spectral-model predictive static programming (MPSP) and, because of its similarity with the pseudo-spectral philosophy, it is renamed as "pseudo-spectral MPSP." Extensive simulation studies with different engagement scenarios illustrate the effectiveness of the proposed guidance to engage with incoming high-speed ballistic targets.